Olha Tarasenko. Greetings from Borys Grinchenko Kyiv University - Tarasenko, Olha (Young Scholars Grinchenko – Seton International Journal, 2021)
Greetings to the authors of the first issue of the e-zine "Young Scientists Grinchenko - Seton International Journal". We thank Seton Hall University for the partnership in our e-zine. We hope that young scientists from different countries on the pages of our e-zine will be happy to share their research. We sincerely wish all the authors of the articles of the first issue of the e-zine "Young Scientists Grinchenko - Seton International Journal" creative inspiration and exciting new discoveries! We invite young scientists from Europe and the USA to cooperate!